FILTERING CTD DATA IN LOMBOK STRAIT TO KNOWING THE SOUND SPEED AND THERMOCLINE CHARACTERISTICS - Iskandar Prawiro; Ahmadi Ahmadi; Ayip Rivai Prabowo (Indonesian Naval Technology College STTAL, 2021)
Lombok Strait is one of 9 chokepoints (narrow point) of the world. Lombok Strait is also one of the 3 lanes of the Indonesian Archipelagic Sea Lanes (IASL) contained in the IASL II which consists of the Makassar Strait and Lombok Strait. Lombok Strait has a depth of more than 150 meters and is a liaison between the Pacific Ocean and the Indian Ocean is very strategic for the submarine trajectory. So it is very important information about the water column in the Lombok Strait for military war operations needs. Therefore, the validity of accurate data is very important, by way of filtering CTD data. The goal is to know the thermocline characteristics and sound speed in the Lombok Strait. One of the methods used for CTD data filtering is by using Analysis Toolpak. Results from CTD data processing using Analysis Toolpak show that there is a difference between data profiles before and after filtering. It also can be seen that the characteristics of the thermocline of the Lombok Strait from North to South are increasingly tight or thin with a thickness of 146.094 meters to 87.694 meters. While the sound speed characteristics in the Lombok Strait from North to South direction also increasingly tight or thin with the difference in the value of sound speed from 34.547 m/s to 27.538 m/s. The seawater mass in the thermocline layer is thought to have originated from the North Pacific Intermediate Water (NPIW) which enters the Lombok Strait through the northern part of the Lombok Strait with an average salinity of 34,415 psu at an average depth of 42.504 meters. Based on the above data it is very important to filter the CTD data to produce valid and accurate data before further processing. Keywords: Filtering, Lombok Strait, Sound Speed, Thermocline.